Preoperative Three-Dimensional Lung Simulation Before Thoracoscopic Anatomical Segmentectomy for Lung Cancer: A Systematic Review and Meta-Analysis - Xiang, Zhongtian; Wu, Bo; Zhang, Xiang; Feng, Nan; Wei, Yiping; Xu, Jianjun; Zhang, Wenxiong (Frontiers in Surgery, 2022)
Background: Whether the utilization of preoperative three-dimensional (3D) lung simulation can improve the outcomes of segmentectomy for lung cancer (LC) is still controversial. Our meta-analysis was performed to compare preoperative 3D lung simulation with non-3D procedures in terms of perioperative outcomes. Methods: Seven databases (Embase, Ovid Medline, ScienceDirect, PubMed, Web of Science, Cochrane Library and Scopus) were searched for eligible articles. Intraoperative outcomes (conversion, operative time, etc.), postoperative indicators (postoperative hospital stay, total number of complications, etc.) and postoperative complications were endpoints. Results: After applying predefined inclusion criteria, we included 8 studies and 989 patients (3D group: 552 patients; non-3D group: 437 patients) in our meta-analysis. The results of the meta-analysis showed that preoperative 3D lung simulation could significantly decrease the blood loss (mean difference [MD]: -16.21 [-24.95~-7.47]ml, p = 0.0003), operative time (MD: -13.03 [-25.56~-0.50]ml, p = 0.04), conversion rate (conversion from segmentectomy to thoracotomy or lobectomy) (MD: 0.12 [0.03~0.48], p = 0.003), postoperative hospital stay (MD: -0.25 [-0.46~0.04]days, p = 0.02) and total number of complications (MD: 0.59 [0.43~0.82], p = 0.001) compared with non-3D procedures. The number of resected lymph nodes (LNs), postoperative drainage time, postoperative forced expiratory volume in the first second (postoperative FEV1) and postoperative drainage volume were similar in the two groups. Arrhythmia (5.30%), pulmonary air leakage (2.72%), atrial fibrillation (2.20%), pulmonary infection (2.04%) and pneumonia (1.73%) were the top 5 postoperative complications in the 3D group. Conclusions: Preoperative 3D lung simulation was better than non-3D procedures in segmentectomy for LC, with better intraoperative and postoperative outcomes. However, our results should be confirmed in larger prospective randomized controlled trials.